Thermosetting polyimide adhesive material based on silicon-oxygen connection acetenyl aniline end capping

By introducing silicon oxy linking units and 3-ethynyl aniline end capping groups into the thermoset polyimide material, combining low boiling point organic solvents and chemical imidation reactions, the problems of high glass transition temperature and poor solubility of traditional materials are solved, and the preparation of thermoset polyimide prepolymers with low glass transition temperature and high solubility are achieved, widening the processing window of the material and improving performance.

CN119505236APending Publication Date: 2025-02-25JIANGSU OCEAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411745714.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Traditional thermosetting polyimide materials with end capped ethynyl aniline have problems with high glass transition temperature and poor solubility of organic solvents, resulting in a narrow melt processing window and difficult processing.

Method used

A thermosetting polyimide prepolymer with low glass transition temperature was prepared by chemical imidation reaction using polydimethylsiloxane-amino (PDMS-NH2) of siliconoxy-linking units and 3-ethynylaniline (3-EA) as the end group, and a low-boiling organic solvent was used to improve solubility and reduce organic solvent residue in the drying product.

Benefits of technology

The glass transition temperature of the prepolymer was successfully reduced, the melt processing window was broadened, the processing performance and performance advantages of the material were improved, and the organic solvent residue was reduced, and the product quality was improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505236A_ABST
    Figure CN119505236A_ABST
Patent Text Reader

Abstract

The invention discloses a thermosetting polyimide adhesive material based on silicon-oxygen connection acetenyl aniline end capping, which is prepared by adopting a low-boiling-point organic solvent, the glass-transition temperature of a thermosetting polyimide prepolymer before curing is lower and is about 104 DEG C, and the thermosetting polyimide prepolymer can be dissolved in the low-boiling-point organic solvent tetrahydrofuran at a high concentration of 30 wt%; and the cured thermosetting polyimide adhesive has high viscosity to a metal substrate. The 3-ethynylaniline-terminated thermosetting polyimide material prepared by the invention has obvious performance advantages, widens the variety of polyimide materials, and has high application value in the fields of advanced resin-based composite materials, high-performance adhesives and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-performance polymer materials, and in particular to a thermosetting polyimide adhesive material using 3-ethynylaniline as a capping agent and a preparation method thereof. Background Art

[0002] Thermosetting polyimide materials terminated with ethynylaniline are a type of high-performance thermosetting polymer material that can form a three-dimensional network structure through covalent crosslinking. They have attracted much attention in the fields of high-temperature resistant adhesives and advanced resin-based composite materials due to the high cost-effectiveness of the ethynylaniline end-capping group and the fact that the high temperature requirements of the equipment are not too harsh. However, the thermal crosslinking temperature of the ethynylaniline group generally starts to crosslink and solidify between 200-300°C, resulting in a narrow melt processing window for this type of material, and the solubility in solvents is not ideal. To this end, in our previous work, we prepared a new type of ethynyl-terminated thermosetting polyimide based on the monomer 4-phenyl ether-1,3-diamine, and measured the glass transition temperature (T g ) is only 155℃, and the T g The value is as high as 335°C, showing excellent comprehensive performance. In addition, silicone-based polymer materials have been proven to have unique advantages in flexibility, thermal stability, chemical stability, and processing capabilities. Therefore, it is very important to develop ethynylaniline-terminated silicone-based polyimide prepolymers with low glass transition temperature and high solubility, and their high-performance cross-linked curing resin materials. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the traditional ethynylaniline-terminated polyimide prepolymer, such as high glass transition temperature and poor solubility in organic solvents, and to provide a method for preparing a silicone-based thermosetting polyimide material. The present invention first adds liquid PDMS-NH 2 , and a certain amount of low-boiling organic solvent, stir thoroughly until dissolved, then add 6FDA and react at room temperature for 2 to 24 hours, add 3-EA and the remaining mass of solvent to make the solid content of the solution 1 to 50wt%, continue to stir and react at room temperature for 4 to 48 hours to obtain a 3-EA-terminated polyimide acid solution. Using chemical imidization, acetic anhydride and triethylamine are slowly added to the reaction solution, react at a certain temperature for 1 to 10 hours, pour the reaction solution into excess distilled water to fully wash the precipitate, and then dry it in a vacuum oven to constant weight. The specific experimental process is as follows:

[0004]

[0005] The purpose of the present invention is achieved through the following technical solutions:

[0006] A thermosetting polyimide adhesive material based on ethynylaniline end-capping with silicon-oxygen linkage comprises the following preparation steps: firstly, in a round-bottom flask, liquid polydimethylsiloxane-amino (PDMS-NH 2 ), and a certain amount of low boiling point organic solvent, stir thoroughly until dissolved, then add hexafluorodianhydride (6FDA) to react at room temperature for 2 to 24 hours, 3-ethynylaniline (3-EA) and the remaining mass of organic solvent, so that the solid content of the solution is 1 to 50wt%, continue to stir at room temperature for 4 to 48 hours, and obtain a 3-EA-terminated polyimide acid solution. Chemical imidization is adopted, acetic anhydride and triethylamine are slowly added to the reaction solution, react at 0 to 80°C for 1 to 10h, pour the reaction solution into excess distilled water, stir thoroughly and wash with water, and dry in a vacuum oven at 40 to 80°C to constant weight after precipitation.

[0007] To further achieve the purpose of the present invention, preferably, the polydimethylsiloxane-amino (PDMS-NH 2 ), and its weight average molecular weight is 248.5, 770, 1600, 2500, 60000, 115000, 200000 or more monomers copolymerized.

[0008] Furthermore, the low boiling point organic solvent described in the step is a mixture of one or more of 1,4-dioxane, chloroform or tetrahydrofuran.

[0009] Further: the PDMS-NH 2 The molar ratio of 6FDA and 3-EA is m:(m+1):2, where m is 0.5-20.

[0010] The thermosetting polyimide material obtained by the preparation method is a thermosetting polyimide prepolymer with 3-EA as a capping group and a cured resin, as well as an adhesive application.

[0011] Compared with the prior art, the present invention has the following advantages and beneficial effects: (1) Considering that the 3-EA-terminated thermosetting polyimide prepolymer begins to crosslink at about 200°C, a higher post-drying treatment temperature cannot be used. For this reason, the present invention uses low-boiling-point 1,4-dioxane (boiling point of 101°C), chloroform (boiling point of 61.2°C) or tetrahydrofuran (boiling point of 66°C) as solvents, replacing traditional high-boiling-point organic solvents such as N-methylpyrrolidone (boiling point of 203°C) and dimethylacetamide (boiling point of 166°C). The organic solvent residue of the product can be reduced during the drying process, and the quality of the prepolymer powder is also improved. (2) Considering that the 3-EA-terminated thermosetting polyimide prepolymer begins to crosslink at about 200°C, the melt processing window is very narrow. For this reason, the present invention uses PMDS-NH containing a silicon-oxygen linking unit. 2 , reducing the glass transition temperature of the prepolymer and widening the melt processing window. The present invention can enrich the types of thermosetting polyimide materials, enhance their performance advantages, and has application potential in high-performance adhesives. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is a real photo of the thermosetting polyimide prepolymer powder based on silicon-oxygen linked ethynylaniline end-capping prepared in Example 1.

[0013] Figure 2 This is the infrared characteristic peak spectrum of the thermosetting polyimide prepolymer powder based on silicon-oxygen-linked ethynylaniline end-capping prepared in Example 1. Wave number 1107 cm -1 Attributed to PDMS-NH 2 Si-O bond, wave number 1366cm -1 The CN stretching vibration peak attributed to the imide ring has a wave number of 1483 cm -1 Assigned to CF bond, wave number 1600cm -1 The peak wave number attributed to the vibration of benzene ring is 1780cm -1 and 1720cm -1 The vibration peak attributed to C=O in the imide ring is 3300 cm -1 The peaks are attributed to the CH vibration peaks in the ethynylaniline capping agent, which proves the successful preparation of the silicon-oxygen linked ethynylaniline capped polyimide prepolymer.

[0014] Figure 3 The temperature rise curve of the thermosetting polyimide prepolymer powder prepared in Example 1 using differential scanning calorimetry shows that the glass transition temperature of the prepolymer is only 104°C, which is lower than similar systems currently reported, and has a significant effect. At the same time, the powder begins to cure and cross-link at around 200°C to generate a thermosetting polyimide resin.

[0015] Figure 4 This is a photo of the thermosetting polyimide prepolymer powder prepared in Example 1 with a solid content of 30 wt % in tetrahydrofuran solvent. It can be seen that the prepolymer powder is completely dissolved.

[0016] Figure 5 This is a physical picture of the solution of the thermosetting polyimide prepolymer powder based on silicon-oxygen bonded ethynylaniline end-capping prepared in Example 1 coated on the surface of a metal sheet.

[0017] Figure 6 for Figure 5 The metal sheet with glue is cured at 300℃ for 1 hour, and the performance of bonding strength is shown in the actual picture. It can bear a 100g weight in the horizontal direction.

[0018] Figure 7 for Figure 5 The metal sheet with glue is cured at 300℃ for 1 hour, and the performance of the bonding strength is shown in the actual picture. It can lift a 5kg weight in the vertical direction. DETAILED DESCRIPTION

[0019] In order to better understand the present invention, the technical solution of the present invention is further described below in conjunction with embodiments and drawings, but the implementation mode of the present invention is not limited thereto.

[0020] Example 1

[0021] Under nitrogen protection, 0.005 mol (1.243 g) PDMS-NH 2 (M w ≈248.5g / mol) and a certain amount of 1,4-dioxane (23.4g), stir and dissolve thoroughly, then add 0.01mol (4.442g) 6FDA and react at room temperature for 6 hours, add 0.01mol (1.172g) 3-EA and the remaining mass of 1,4-dioxane (2.6g), so that the solid content of the solution is 20wt%, continue to stir and react at room temperature for 16 hours, and obtain a 3-EA-terminated polyimide acid solution. Using chemical imidization, 3.063g (0.03mol) acetic anhydride and 3.035g (0.03mol) triethylamine are slowly added to the reaction solution, react at room temperature for 6h, and the homogeneous solution is poured into 100mL distilled water to be fully washed and precipitated. The synthesized product is washed and filtered with excess distilled water for a total of 3 times, and then dried in a vacuum oven at 60°C for at least 24h to constant weight to obtain an off-white powder product with a yield of 98.5%.

[0022] Example 2

[0023] Under nitrogen protection, 0.005 mol (1.243 g) PDMS-NH2 (M w ≈248.5g / mol) and a certain amount of 1,4-dioxane (10.2g), stir and dissolve thoroughly, then add 0.01mol (4.442g) 6FDA and react at room temperature for 10 hours, 0.01mol (1.172g) 3-EA and the remaining mass of 1,4-dioxane, so that the solid content of the solution is 30wt%, continue to stir and react at room temperature for 24 hours, and obtain a 3-EA-terminated polyimide acid solution. Using chemical imidization, 3.063g (0.03mol) acetic anhydride and 3.035g (0.03mol) triethylamine are slowly added to the reaction solution, react at 50℃ for 6h, and the homogeneous solution is poured into 100mL distilled water for thorough washing and precipitation. The synthesized product is washed and filtered with excess distilled water for a total of 3 times, and then dried in a vacuum oven at 60℃ for at least 24h to constant weight to obtain an off-white powder product with a yield of 96.8%.

[0024] Example 3

[0025] Under nitrogen protection, 0.01 mol (2.49 g) PDMS-NH 2 (M w ≈248.5g / mol) and a certain amount of 1,4-dioxane (30g), stir and dissolve thoroughly, then add 0.015mol (6.66g) 6FDA and react at room temperature for 8 hours, add 0.01mol (1.172g) 3-EA and the remaining mass of 1,4-dioxane, so that the solid content of the solution is 20wt%, continue to stir and react at room temperature for 24 hours, and obtain a 3-EA-terminated polyimide acid solution. Chemical imidization was adopted, 3.063g (0.03mol) acetic anhydride and 3.035g (0.03mol) triethylamine were slowly added to the reaction solution, reacted at 60℃ for 7h, and the homogeneous solution was poured into 200mL distilled water for thorough washing and precipitation. The synthesized product was washed and filtered with excess distilled water for a total of 3 times, and then dried in a vacuum oven at 60℃ for at least 24h to constant weight to obtain an off-white powder product with a yield of 99.1%.

[0026] Example 4

[0027] Under nitrogen protection, 0.01 mol (7.7 g) PDMS-NH 2 (M w≈770g / mol) and a certain amount of 1,4-dioxane (50g), stir and dissolve thoroughly, then add 0.015mol (6.66g) 6FDA and react at room temperature for 8 hours, add 0.01mol (1.172g) 3-EA and the remaining mass of 1,4-dioxane, so that the solid content of the solution is 1wt%, continue to stir and react at room temperature for 24 hours, and obtain a 3-EA-terminated polyimide acid solution. Using chemical imidization, 3.063g (0.03mol) acetic anhydride and 3.035g (0.03mol) triethylamine are slowly added to the reaction solution, react at 60℃ for 7h, and the homogeneous solution is poured into 200mL distilled water for thorough washing and precipitation. The synthesized product is washed and filtered with excess distilled water for a total of 3 times, and then dried in a vacuum oven at 60℃ for at least 24h to constant weight to obtain an off-white powder product with a yield of 96.9%.

[0028] Example 5

[0029] Under nitrogen protection, 0.005 mol (1.243 g) PDMS-NH 2 (M w ≈248.5g / mol) and a certain amount of tetrahydrofuran (23.4g), fully stirred and dissolved, then added 0.01mol (4.442g) 6FDA to react at room temperature for 6 hours, 0.01mol (1.172g) 3-EA and the remaining mass of tetrahydrofuran (2.6g), so that the solid content of the solution is 20wt%, continued to stir and react at room temperature for 16 hours, and obtained a 3-EA-terminated polyimide acid solution. Chemical imidization was adopted, 3.063g (0.03mol) acetic anhydride and 3.035g (0.03mol) triethylamine were slowly added to the reaction solution, reacted at room temperature for 6h, the homogeneous solution was poured into 100mL distilled water and fully washed and precipitated, the synthesized product was washed and filtered with excessive distilled water for a total of 3 times, and then dried in a vacuum oven at 80°C for at least 24h to constant weight to obtain an off-white powder product with a yield of 97.5%.

[0030] Example 6

[0031] Under nitrogen protection, 0.01 mol (7.7 g) PDMS-NH 2 (M w≈770g / mol) and a certain amount of chloroform (50g), stir and dissolve thoroughly, then add 0.015mol (6.66g) 6FDA and react at room temperature for 8 hours, add 0.01mol (1.172g) 3-EA and the remaining mass of chloroform, so that the solid content of the solution is 1wt%, continue to stir and react at room temperature for 24 hours, and obtain a 3-EA-terminated polyimide acid solution. Using chemical imidization, 3.063g (0.03mol) acetic anhydride and 3.035g (0.03mol) triethylamine are slowly added to the reaction solution, react at 60℃ for 7h, and the homogeneous solution is poured into 200mL distilled water for thorough washing and precipitation. The synthesized product is washed and filtered with excess distilled water for a total of 3 times, and then dried in a vacuum oven at 60℃ for at least 24h to constant weight to obtain an off-white powder product with a yield of 98.9%.

[0032] The above are all preferred embodiments of the present invention. For ordinary technicians in this technical field, without departing from the principle of the present invention, various equivalent modifications to the present invention belong to the protection scope of the claims attached to this application.

Claims

1. A thermosetting polyimide adhesive material based on silane-connected ethynylaniline end-capping, characterized in that: The specific molecular structure is as follows:

2. According to claim 1, a thermosetting polyimide adhesive material based on silicon-oxygen-linked ethynylaniline end-capping, the specific preparation method is: under nitrogen protection, in a round-bottom flask, first add liquid polydimethylsiloxane-amino PDMS-NH2 and a certain amount of low-boiling point organic solvent, stir thoroughly until dissolved, then add hexafluorodianhydride 6FDA to react at room temperature for 2 to 24 hours, 3-ethynylaniline 3-EA and the remaining mass of the solvent, so that the solid content of the solution is 1 to 50wt%, continue to stir at room temperature for 4 to 48 hours to obtain a 3-EA end-capped polyimide acid solution; adopt chemical imidization, slowly add acetic anhydride and triethylamine to the reaction solution, react at 0 to 80°C for 1 to 10h, pour the reaction solution into excess distilled water, stir thoroughly and wash with water, and after precipitation, dry in a vacuum oven at 40 to 80°C to constant weight.

3. A thermosetting polyimide adhesive material based on silicon-oxygen linked ethynylaniline termination according to claim 2, characterized in that: The polydimethylsiloxane-amino PDMS-NH2 in the step has a weight average molecular weight M w It is formed by copolymerization of one or more monomers with a size of 248.5, 770, 1600, 2500, 60000, 115000, 200000 g / mol.

4. A thermosetting polyimide adhesive material based on silicon-oxygen linked ethynylaniline termination according to claim 2, characterized in that: The low boiling point organic solvent described in the step is a mixture of one or more of 1,4-dioxane, chloroform or tetrahydrofuran.

5. The thermosetting polyimide adhesive material based on silicon-oxygen linked ethynylaniline termination according to claim 2, characterized in that: The molar ratio of PDMS-NH2, 6FDA and 3-EA described in the steps is m:(m+1):2, wherein m is 0.5-20.

6. A thermosetting polyimide material based on silicon-oxygen linked ethynylaniline end-capping obtained according to any one of claims 1 to 5, characterized in that: Application in adhesives.

Citation Information

Patent Citations

  • Thermosetting silicon-containing polyimide resin prepolymer, resin and preparation method thereof

    CN115975191A

  • Polyimide resin composition

    JP1998231426A

  • Acetylenic end-capped polyimides

    US5290908A